2016
DOI: 10.1186/s13049-016-0313-5
|View full text |Cite
|
Sign up to set email alerts
|

Unmanned aerial vehicles (drones) in out-of-hospital-cardiac-arrest

Abstract: BackgroundThe use of an automated external defibrillator (AED) prior to EMS arrival can increase 30-day survival in out-of-hospital cardiac arrest (OHCA) significantly. Drones or unmanned aerial vehicles (UAV) can fly with high velocity and potentially transport devices such as AEDs to the site of OHCAs. The aim of this explorative study was to investigate the feasibility of a drone system in decreasing response time and delivering an AED.MethodsData of Global Positioning System (GPS) coordinates from historic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
158
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(163 citation statements)
references
References 12 publications
0
158
0
5
Order By: Relevance
“…However, previous research on drone-delivered AEDs is limited to three studies, all of which are based on covering-type location models. Two of these studies focus solely on optimizing drone base locations without considering system congestion (Pulver et al 2016, Claesson et al 2016). The third paper considers both optimal base locations and system congestion, where a queuing model to determine the number of drones required at each base is solved after the base locations have been optimized (Boutilier et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous research on drone-delivered AEDs is limited to three studies, all of which are based on covering-type location models. Two of these studies focus solely on optimizing drone base locations without considering system congestion (Pulver et al 2016, Claesson et al 2016). The third paper considers both optimal base locations and system congestion, where a queuing model to determine the number of drones required at each base is solved after the base locations have been optimized (Boutilier et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These first-responder programs might be effective in out-of-hospital settings. Particularly in public locations, the use of drones with a public-access AED can substantially reduce the AED delivery time to a location where an OHCA may be occurring [34,35]. Because the proportion of VF arrests decreases as the rhythm assessment by defibrillators is delayed [36], more patients in OHCA would benefit from PAD if public-access AED pads were attached earlier.…”
Section: Discussionmentioning
confidence: 99%
“…In emergency medicine, studies have showed that the use of drones may prove to be safe and feasible for delivering an automated external defibrillator (AED) for out-of-hospital cardiac arrests (OHCA) in areas identified using GIS (Geographic Information System) models. 18 The various methods of delivering an AED after arrival onsite while keeping the drones within the line of sight were further studied. This study showed that the use of an AED-equipped drone might have the potential to reduce the time to defibrillation for OHCA.…”
Section: Potential Applicationsmentioning
confidence: 99%